ANTESEDEN BRAND LOYALTY PADA PENGGUNA APLIKASI JUAL BELI ONLINE DI JAKARTA - Andri Reynaldi Zagoto; Sri Vandayuli Riorini (STMIK Widuri Jakarta, 2025)
This study aims to analyze the factors influencing brand loyalty among users of online shopping platforms in Jakarta. The primary focus of this research is to examine the impact of brand satisfaction, emotional brand attachment, and brand love on brand loyalty.The research employs a quantitative approach with hypothesis testing. Data collection was conducted through an online survey using purposive sampling on 230 respondents who have been using e- commerce applications for at least three months. Variables were measured using a Likert scale of 1–5. Validity testing was carried out using Confirmatory Factor Analysis (CFA) with a factor loading threshold of ≥ 0.35, while reliability testing was conducted using Cronbach’s Alpha with a threshold of ≥ 0.6. The findings indicate that brand satisfaction has a positive and significant influence on emotional brand attachment and brand love. Emotional brand attachment positively affects brand love but does not directly impact brand loyalty. Additionally, brand love is proven to have a positive influence on brand loyalty. These findings suggest that consumer satisfaction can enhance brand loyalty through emotional attachment and brand love. Therefore, marketing strategies that strengthen emotional connections with consumers play a crucial role in building brand loyalty in e-commerce platforms.